Vicarious intergroup contact and the role of authorities in prejudice reduction - Gómez, Ángel; Huici, Carmen (The Spanish Journal of Psychology, 2008)
The present study focuses on the effect of vicarious intergroup contact and the support of an authority figure on the improvement of outgroup and meta-stereotype evaluations. Meta-stereotype refers to the shared beliefs of ingroup members about how they consider outgroup members to perceive their group. Three preliminary studies were carried out to determine desirable and undesirable characteristics for a good basketball performance, the task that best demonstrates the application of these characteristics, and the two groups (basketball teams) that should be involved in the vicarious intergroup contact. Fans of one of the basketball teams participated in the current study. Vicarious intergroup contact improved outgroup and meta-stereotype evaluations as compared with a no contact condition. In addition, the positive effects of vicarious intergroup contact significantly increased when it was supported by an authority figure. More importantly, our study also shows that the improvement of outgroup evaluation was partially mediated by changes on meta-stereotypes.
Keywords: Vicarious intergroup contact; Authority figure; Prejudice reduction; Metastereotypes; Perceived outgroup bias